Pulmonary vein isolation for the treatment of atrial fibrillation: past, present and future. (January 2010) - le Polain de Waroux, Jean-Benoîît; Talajic, Mario; Khairy, Paul; Guerra, Peter G; Roy, Denis; Thibault, Bernard; Dubuc, Marc; Macle, Laurent
Atrial fibrillation is the most common sustained cardiac arrhythmia and is associated with impaired quality of life and an increased risk of stroke and mortality. Antiarrhythmic drugs, currently the first-line therapy for patients without permanent atrial fibrillation, fail to prevent recurrences in over 50% and are associated with significant adverse effects. In the majority of cases, atrial fibrillation arises from the repetitive firing of myocytes in muscle sleeves that extend from the left atrium into the pulmonary veins. Pulmonary vein isolation has emerged as an effective treatment in selected patients. In this paper, the past and present roles of pulmonary vein isolation are described and the future developments of this technique are explored.